Epidemiology of breast cancer in women based on diagnosis data from oncologists and senologists in Algeria - F Smaili; A Boudjella; A Dib; S Braikia; H Zidane; R Reggad; A Bendib; A Abdelouahab; F Bereksi-Reguig; D Yekrou; A Bentouati; T Filali; et al. (Cancer Treatment and Research Communications, 2020)
Background: Breast cancer (BC) is a major health issue threatening women's life. No reliable epidemiological data on BC diagnosed by oncologists/senologists are available in Algeria. Methods: The BreCaReAl study, a non-interventional prospective cohort study, included adult women with confirmed BC in Algeria. Disease incidence, patients and disease characteristics, treatment patterns, and mortality rate were recorded up to 12 months of follow-up. Results: Overall, 1,437 patients were analysed: median age was 48 [41;57] years and 337 (23.5%) women had a family history of BC. BC incidence was 22.3 (95% CI: 21.5; 23.2) cases per 100,000 inhabitants over 8 months. Delayed diagnosis was reported in 400 (29.2%) patients. First line of treatments were mainly chemotherapy and surgery. Twenty-eight serious adverse events were reported including 10 (37.0%) events which led to death. Mortality rate reached 3.2% at 12 months Conclusion: A delayed diagnosis highlights the importance of implementing more effective screening strategies.